Preparation and properties of carbon nanotube/binary‐polymer composites with a double‐segregated structure. Issue 2 (12th August 2013) - Pang, Huan; Bao, Yu; Yang, Shu‐Gui; Chen, Chen; Zhang, Wei‐Qin; Chen, Jun; Ji, Xu; Lei, Jun
ABSTRACT A carbon nanotube (CNT)/poly(methyl methacrylate) (PMMA)/ultrahigh molecular weight polyethylene (UHMWPE) composite containing a double‐segregated structure was formalized by means of a facile mechanical mixing technology. In the composite, the CNTs were decorated on the surfaces of PMMA granules, and the CNTs decorated granules formed the continuous segregated conducting layers at the interfaces between UHMWPE particles. Morphology observations confirmed the formation of a specific double‐segregated CNT conductive network, resulting in an ultralow percolation threshold of ∼0.2 wt %. The double‐segregated composite containing only 0.8 wt % CNT loading exhibited a high electrical conductivity of ∼0.2 S m−1 and efficient electromagnetic shielding effectiveness of ∼19.6 dB, respectively. The thermal conductivity, temperature‐resistivity behaviors, and mechanical properties of the double‐segregated composites were also studied. This work provided a novel conductive network structure to attain a high‐performance conducting polymer composite at low filler loadings. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 39789.